Relationship between time management skills and anxiety and academic motivation of nursing students in Tehran - Arezoo Mohamadkhani Ghiasvand; Manijeh Naderi; Mansoureh Zagheri Tafreshi; Farzane Ahmadi; Meimanat Hosseini (Electronic Physician, 2017)
Introduction: Time management skills are essential for nursing students’ success, and development of clinical competence. The purpose of this study was to determine the relationship between time management skills and anxiety and academic motivation of nursing students in Tehran medical sciences universities in 2015. Methods: This cross-sectional study was carried out on 441 nursing students in three medical universities in Tehran. Random stratified sampling was done to select the samples. Data were collected using demographic Questionnaire, Time Management Questionnaire (TMQ), Spielberger State-Trait Anxiety Inventory (STAI) and Academic Motivation Scale (AMS), which was completed t by self-report. Data were analyzed using SPSS 18 software with descriptive and analytical statistics such as ANOVA, independent t-test, Regression and Pearson Correlation Coefficient. Results: Most participants had a moderate level of time Management skills (49%), State Anxiety (58%), Trait Anxiety (60%) and Academic Motivation (58%). The results also showed a statistically significant negative correlation between the students’ TMQ scores and the state anxiety (r= -0.282, p< 0.001) and trait anxiety scores (r= -0.325, p<0.001). Moreover, there was a statistically significant positive correlation between the students’ TMQ scores and AMS scores (r= 0.279, p< 0.001). Conclusion: Regarding the findings, it seems that it is necessary to plan for improving time management skills in order to enhance academic motivation and reduce anxiety rates among nursing students